Targeting compensatory proliferation signals in oral cancer - Loganathan Kavitha; Vijayashree Priyadharsini J; Anitha P; Paramasivam A (Journal of Oral Biology and Craniofacial Research)
Apoptosis is an orchestrated phenomenon that regulates cell populations in physiological and pathological conditions. Carcinogenesis involves a state of disequilibrium between cell proliferation and cell death. The resistance to conventional therapeutic modalities of cancer, including surgery, radiotherapy, and chemotherapy, can be explained by the compensatory repair and regeneration that occurs in the tumor microenvironment following apoptosis through the apoptotic compensatory proliferation signaling microvesicles (ACPSVs) or apoptotic extracellular microvesicles (ApoEVs). These microvesicles provide proliferative signals and act as mutagens, triggering cell proliferation, angiogenesis, immune evasion, metastasis, and invasion. This review discusses the phenomenon of apoptosis-induced proliferation and the role of ApoEVs in establishing an oncoregenerative niche, resulting in therapeutic resistance and recurrence of malignancies.